Recombinant human Fab to glycoprotein D neutralizes infectivity and prevents cell-to-cell transmission of herpes simplex viruses 1 and 2 in vitro. - Burioni, R (1994)
Herpes simplex viruses 1 and 2 (HSV-1 and -2) are associated with a number of conditions of varying severity, which are only partially responsive to current therapies. Human antibodies to the viruses offer a potential alternative. We describe here the generation of panels of human monoclonal Fab fragments to HSV-1 and -2 by panning a phage display combinatorial antibody library against whole lysates from the two viruses. Each lysate selected a largely distinct set of Fabs, although all of the Fabs were cross-reactive with both viruses. In a plaque-reduction assay, one Fab neutralized HSV-1 at 0.25 microgram/ml (50% reduction) and HSV-2 at 0.05 microgram/ml. This Fab also inhibited plaque formation when applied to virus-infected monolayers, completely abolishing HSV-2 plaque development at 25 micrograms/ml 72 hr postinfection, indicating the ability of the Fab to prevent cell-to-cell spread of virus. The Fab was shown to recognize viral glycoprotein D and to neutralize virus primarily by a postattachment mechanism. Recombinant Fabs may be useful for topical administration, although whole antibody will probably be required for systemic use.